Composing place : digital rhetorics for a mobile world - Greene, Jacob (Jacob Wes) (Logan : Utah State University Press, 2023)
"Composing Place proposes an innovative approach to engaging with the compositional affordances of mobile technologies. Jacob Greene utilizes a rhetorical framework through which writers can leverage the affordances of new technologies and develops this framework by drawing on theoretical approaches within rhetorical studies, multimodal composition, and spatial theory" --
Front Matter -- Contents -- Preface -- Acknowledgments -- Making (Do) With Emerging Technologies of Digital Writing -- Theories of Mobile Writing -- Assembling Publics xWith Mobile Media -- Articulated Agencies of Mobile Writing -- Practices of Mobile Writing -- Refractions -- Layers -- Margins -- Pedagogies of Mobile Writing -- From Mobile-First to Place-First -- Mobile Writing as Public Pedagogy -- References -- Index -- About the Author
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 09, 2023).
JSTOR
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Technological innovations; Mobile computing -- Technological innovations; Mobile computing -- Social aspects; Mobile communication systems -- Technological innovations; Mobile communication systems -- Social aspects; Mobile communication systems in education; Spatial behavior -- Social aspects; Informatique mobile -- Innovations; Informatique mobile -- Aspect social; Radiocommunications mobiles -- Innovations; Radiocommunications mobiles -- Aspect social; Apprentissage mobile; Rhetoric; Technical Writing; TECHNOLOGY & ENGINEERING; Mobile communication systems in education; Mobile communication systems -- Technological innovations; Electronic books